Handbook of research on advancements of artificial intelligence in healthcare engineering - Sisodia, Dilip Singh 1977-; Pachori, Ram Bilas 1979-; Garg, Lalit 1977- (IGI Global, 2020)
"This book explores the possible applications of machine learning, deep learning, soft computing, and evolutionary computing techniques in the design, implementation, and optimization of challenging healthcare engineering solutions"--